2019
DOI: 10.1101/577049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Treatment Failure among People living with HIV taking Antiretroviral Therapy in Ethiopia

Abstract: Background: Although treatment failure (TF) among population on antiretroviral therapy (ART) become a major public health threat, its magnitude of and factors leading to it are poorly defined. Hence, we aimed to estimate the magnitude of TF and its determinants in Ethiopia. Methods:A follow-up study was conducted from March 2016 to 2017. Clinical and laboratory data were captured from paticipants' medical record. Socio-demographics and explanatory variables were collected using structured questionnaire. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
1
10
4
Order By: Relevance
“…However, this contradicts with other study conducted at Rohde Island which showed 43% viral suppression among pediatric population [14]. This study revealed that pediatric TF is a programmatic concern since there is significant difference with VLS among pediatric versus adult in Ethiopia which was reported as 88.1% [23]. Immunologic failure at base line of this study was 185 (33.3%) at ART initiation and improved to 39 (7%) after 80 month of ART experience.…”
Section: Discussioncontrasting
confidence: 81%
“…However, this contradicts with other study conducted at Rohde Island which showed 43% viral suppression among pediatric population [14]. This study revealed that pediatric TF is a programmatic concern since there is significant difference with VLS among pediatric versus adult in Ethiopia which was reported as 88.1% [23]. Immunologic failure at base line of this study was 185 (33.3%) at ART initiation and improved to 39 (7%) after 80 month of ART experience.…”
Section: Discussioncontrasting
confidence: 81%
“…The most higher WHO clinical stage of HIV was stage 3 in this study, which is dissimilar to study done in India in 2019 in which the most common unsuppressed patients were in stage 1 (23) The virological failure was observed in the age group 39-48 years, which is similar to the nding of the study done in Ethiopia in which virological failure was observed among patients aged < 35 years (20) Most of patients 82.1% had suppressed viral load (non detectable copies/ ml and less than 40 copies/ ml) because viral load usually become not detected after 12 3 month successful treatment, while patients with unsuppressed viral load may need a good adherence, they may have metabolic problems or they may have drug resistance mutations. This nding put Sudan closer to the UNAIDS treatment target 2020 in which 90% of patients under treatment must have suppressed viral load.…”
Section: Discussioncontrasting
confidence: 76%
“…Regarding sex status, the number of males were higher than females (58% versus 42%) in this study, which is similar to study done in Sudan in 2015 in which males were higher (22) , however it was dissimilar to the study done in Ethiopia in 2019 in which the females were higher in number (20) .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In sub-Saharan African countries, viral load suppression rate was 40.2-77.4% [10], and 24% of the adult patients on first-line ART experienced virological failure within 12 months of ART initiation [11]. In the Ethiopian public health facilities, virological failure was estimated to be 11.9% [12]. Ethiopia has adopted the UNAIDS 90-90-90 treatment target by 2020 [13], and other countries have planned to reach 90% viral suppression among all people receiving ART [5].…”
Section: Introductionmentioning
confidence: 99%